2008
DOI: 10.1007/978-3-540-87531-4_5
|View full text |Cite
|
Sign up to set email alerts
|

An Infinite Automaton Characterization of Double Exponential Time

Abstract: Abstract. Infinite-state automata are a new invention: they are automata that have an infinite number of states represented by words, transitions defined using rewriting, and with sets of initial and final states. Infinite-state automata have gained recent interest due to a remarkable result by Morvan and Stirling, which shows that automata with transitions defined using rational rewriting precisely capture context-sensitive (NLINSPACE) languages. In this paper, we show that infinite automata defined using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…As corollaries of our results, we show the closure under complement for ordered Mvpa that was open 1 and an algorithm in time 2 (n+log |A|)2 O(d) to check the emptiness for bounded-phase Mvpa, improving the 2 |A| 2 O(d) bound shown in [11,12] and matching the bound that can be derived from the results of [9].…”
Section: Introductionsupporting
confidence: 73%
“…As corollaries of our results, we show the closure under complement for ordered Mvpa that was open 1 and an algorithm in time 2 (n+log |A|)2 O(d) to check the emptiness for bounded-phase Mvpa, improving the 2 |A| 2 O(d) bound shown in [11,12] and matching the bound that can be derived from the results of [9].…”
Section: Introductionsupporting
confidence: 73%
“…This is done by adapting a construction in [10], where it is shown that certain bounded-phase pushdown-transducer automata capture precisely the class 2ETIME.…”
Section: Emptiness Of Mpda Is 2etime-hardmentioning
confidence: 99%
“…The run is accepting if all leaf configurations are accepting. Following the idea of [10], we write the labeled tree as the string (let c r denote the reverse of c) It is generated by the (sketched) context-free grammar…”
Section: Theorem 12 the Emptiness Problem For Mpda Is 2etime-hard Unmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, results from [6,7,16] imply that MSO model-checking for S is decidable and results from [5,7] imply that model-checking linear-time temporal logic formulas can be solved in double exponential time. This is optimal, since reachability of k-phase multi-pushdown systems is double exponential time hard [14].…”
Section: Decidabilitymentioning
confidence: 99%